Synthesis and Characterization of Corn Starch Phthalate by a Semidry Method. (31st May 2019) - Yang, Chengdong; Lin, Yi; Cheng, Fei; Zhou, Mi; Tan, Lin; Zhu, Puxin
Abstract : Starch phthalate (SP) with plasticity and hydrophobicity can have a better adhesion to aromatic polyesters compared with other esterified starch. Hence, modification of corn starch with phthalic anhydride (PA) is carried out by using a semidry method, and the product SP with varied degrees of substitution (DS) is characterized by group titration, Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), scanning electron microscope (SEM), rapid viscosity analysis, thermogravimetric analysis, film transmittance test, and water contact angle measurement. The results show that a small amount of N, N‐dimethylformamide (DMF) as the solvent for dissolving PA can help to greatly increase the DS of the SP samples. The phthalate group is successfully introduced into starch structure by the semidry method under the recommended reaction conditions of 150 °C for 2 h. Compared with native corn starch, SP samples have lower values of crystallinity, paste viscosity, retrogradation, and thermal degradation temperature, and higher values of carbon residue in thermal decomposition, of transparency and hydrophobicity for the films. Due to these good characteristics, the modified starch, SP, may have great potential applied in starch film, adhesives, textile sizes, and so on. Abstract : Compared with native corn starch, starch phthalate (SP) samples have lower values of crystallinity, paste viscosity, retrogradation, and thermal degradation temperature, and higher values of carbon residue in thermal decomposition, of transparency and hydrophobicity for the films. Due to these good characteristics, the modified starch, SP, may have great potential applied in starch film, adhesives, textile sizes, and so on.